Identity (Trans)formation in Croatian Community in Burgenland - Ščukanec, Aleksandra (2011)
Burgenland Croats are members of Croatian minority whose forefathers left their homeland 500 years ago and settled in former West Hungary, Lower Austria and southern parts of Moravia. Today they mostly live in the Austrian province Burgenland where they managed to preserve their language and culture for several centuries. But in the last few decades the number of speakers has significantly decreased. Burgenland Croatian is a part of the UNESCO’s list of endangered languages, and the current situation poses many challenges for Burgenland Croats regarding their future. In our study of German-Croatian language contacts in Burgenland we have also focused on the question of identity in this Croatian community. Our main objective was to analyze the ways in which Burgenland Croats express their personal experience and attitudes towards cultural and lingual identity as a minority group. We examined the possibility of drawing some general conclusions regarding Burgenland-Croatian identity by means of reconstructing language biographies / narrative interviews of individual speakers. The elicited data indicate that the age, place of birth and family background, together with language, i.e. mother tongue, are the parameters which play the crucial role in identity formation and the realisation of attitudes towards (multi)cultural identity. Language biographies proved to be a useful methodological tool when analyzing the construction of (double) identity because both implicitly and explicitly, they reveal subjective reflections of the informants, which enabled us to make the study as close to the real situation in Burgenland as possible.